Factor influence job satisfaction among the employees : a case study at WIDAD Education Sdn Bhd / A’idah Salleh - Salleh, A’idah (2019)
The successful of a company has been link to achieve job satisfaction at a higher level. WIDAD Education Sdn Bhd needs to provide job satisfaction based on supervision, commitment, teamwork among colleagues, working environment and sense of belonging. The measurement of job satisfaction among the employees at WIDAD Education Sdn Bhd is based on a survey of 138 employees and analyzed using the Statistical Package for the Social Sciences (SPSS). The objective of this research is to investigate the factors that contributed to job satisfaction among the employees at WIDAD Education Sdn Bhd. The researcher has conduct descriptive research which describe job satisfaction obtain based on questionnaire respond by the respondents. The result show, supervision, sense of belonging and working environment are significant to job satisfaction, whereas commitment and teamwork among colleagues are not significant to the job satisfaction among the employees at WIDAD Education Sdn Bhd. It appears that the result shows that the hypotheses accepted only for supervision, sense of belonging and working environment which had strong relationship with job satisfaction. While the hypotheses for commitment and teamwork among colleagues are rejected for this study.